2019
DOI: 10.1016/j.bbmt.2018.12.442
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin Prophylaxis for Autologous Stem Cell Transplant: A Second Look

Abstract: Background: Our group previously reported a 16% incidence of HC after hematopoietic cell transplantation (HCT) involving mostly matched unrelated donors (85%) and ATG-containing regimens (80%) (Silva, Haematologica 2010). PT-Cy is an effective GVHD prophylaxis in haplo-or matched unrelated transplants. There is a paucity of information about the risk of HC in this setting. Objective: To retrospectively assess the incidence and clinical factors associated with HC in alloHCT recipients receiving PTCy as GVHD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
4
7
0
Order By: Relevance
“…Although this is not a prospective randomized controlled study, these results reflect the significant positive impact of levofloxacin prophylaxis at our institution and can be compared with prior reports in the autologous HSCT population (Table 7) who did not receive prophylaxis. [18][19][20][21][22][23][24] In our study, multivariate analysis confirmed that absence of levofloxacin prophylaxis was independently and significantly associated with higher rates of both FN and BSI. Levofloxacin prophylaxis furthermore did not result in a difference in C difficile infections, length of stay, or death at 30-or 100-days post-HSCT in the present study, consistent with findings in other studies.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Although this is not a prospective randomized controlled study, these results reflect the significant positive impact of levofloxacin prophylaxis at our institution and can be compared with prior reports in the autologous HSCT population (Table 7) who did not receive prophylaxis. [18][19][20][21][22][23][24] In our study, multivariate analysis confirmed that absence of levofloxacin prophylaxis was independently and significantly associated with higher rates of both FN and BSI. Levofloxacin prophylaxis furthermore did not result in a difference in C difficile infections, length of stay, or death at 30-or 100-days post-HSCT in the present study, consistent with findings in other studies.…”
Section: Discussionsupporting
confidence: 80%
“…As these findings are similar to those from prior studies of fluoroquinolone prophylaxis in autologous HSCT, a reasonable argument for broader use of this intervention has been proposed in this population. [18][19][20][21][22][23][24] Complete suppression of Gram-negative BSI was particularly dramatic in this study and is unique for a study this size.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations